Genomic Data-Sharing Practices. Issue 1 (2019) - Villanueva, Angela G.; Cook-Deegan, Robert; Robinson, Jill O.; McGuire, Amy L.; Majumder, Mary A.
Abstract : Making data broadly accessible is essential to creating a medical information commons (MIC). Transparency about data-sharing practices can cultivate trust among prospective and existing MIC participants. We present an analysis of 34 initiatives sharing DNA-derived data based on public information. We describe data-sharing practices captured, including practices related to consent, privacy and security, data access, oversight, and participant engagement. Our results reveal that data-sharing initiatives have some distance to go in achieving transparency.